Advanced Methods of Managing the Efficiency of Professional Office Duties of Civil Servants - D. V. Simutova (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
One of the most important lines in state governance in Russia is an increase in its effectiveness and one of the utmost goals of state HR management is a rise in efficiency and effectiveness of professional service duties of civil servants. To attain these results is impossible without effective use of advanced methods and ways of influencing the staff of state bodies. The article provides the author's definition of advanced methods of managing the efficiency of professional office duties of civil servants. As potential methods of managing the efficiency of professional office duties of civil servants the author puts forward the following: 1) management by goals and results and the system of balanced indicators; 2) project management; 3) effective contract. As a result of the research these methods were defined as advanced methods of managing the efficiency of professional office duties of civil servants. At the same time serious drawbacks in their practical application were found. The importance of the research is shown by the need to modernize the found advanced methods. Elimination of these drawbacks could allow us not only to adapt these tools to the present day goals of state bodies, but also to raise the efficiency of state governance in general.